Театр и город в зеркале критики (зимний сезон 1912–1913 гг. в Харькове) - Полякова, Ю.Ю. (Харкiвський нацiональний унiверситет iм. В.Н. Каразiна, 2012)
На основе анализа рецензий, опубликованных на страницах харьковских периодических изданий, автор статьи прослеживает взаимоотношения между двумя театрами, руководимыми Н. Н. Синельниковым, зрителями и критиками в зимнем сезоне 1912–1913 гг. Синельников, как режиссер и антрепренер, стремился учитывать разнообразные интересы публики и коммерческую сторону дела, при этом активно участвуя в общественной жизни города. Публика искала в театре не только развлечений, но и ответов на важнейшие вопросы современной жизни. Театральные критики ведущих газет выражали взгляды харьков- ской интеллигенции, желавшей видеть в театре в театре рупор прогрессивных идей и поэтому осуждавшей Синельникова за коммерческий расчет в ведении дела. The author, basing her study on theater reviews published in Kharkiv media, analyzes the interrelation between the two theaters headed by N.N. Sinelnikov, professional critics and the audiences during the 1912—1913 winter season. As a stage director and entrepreneur, N.N. Sinelnikov had to take into due consideration both the interests of different audiences and commercial aspects of his businesses; to complicate things further, he was rather a significant public figure. Spectators of those times expected to get entertained in the theater, but they also wanted to get some of the most important questions of social life answered by the performances. Theater columnists of the leading papers conveyed the views of local intelligentsia who wanted theater to serve as mouthpiece of progressive social ideas, thus condemning Sinelnikov for seeking too much commercial advantage.
Theater and the City Mirrored in Critique (1912–1913 Winter Season in Kharkiv)
Полякова Юліана Юріївна, театрознавець, головний бібліограф Центральної наукової бібліотеки Харківського національного університету імені В. Н. Каразіна.
Keywords: театральная критика; антрепренерская деятельность; Синельников Н.Н.; зрители; репертуар; theater critique; entrepreneur’s activities; Sinelnikov N.N.; audience; repertoire